Impact of cultural intelligence on the cross-cultural adaptation of international students in China: The mediating effect of psychological resilience - Chu, Kequn; Zhu, Fengshu (Frontiers in Psychology, 2023)
Cultural intelligence can affect the cross-cultural adaptation of International students in China, but the mechanism of their influence is still unclear. This study examined the mediating effect of psychological resilience of International students in China in the process of cultural intelligence affecting cross-cultural adaptation. We used the cultural intelligence scale, psychological resilience scale and cross-cultural adaptation scale to measure 624 foreign students in China. Results: (1) There is a significant positive correlation among cultural intelligence, psychological resilience and cross-cultural adaptation of International students in China; (2) Resilience plays a mediating effect in the influence of cultural intelligence of International students in China on cross-cultural adaptation. Conclusion: The cultural intelligence of International students in China can directly affect their cross-cultural adaptation, and can also affect their cross-cultural adaptation through the mediating effect of psychological resilience.